Critical Issues and Trends in Innovation and Entrepreneurship Education in Higher Education in the Post-COVID-19 Era in China and Spain - Yinglong Qiu; Adela García-Aracil; Rosa Isusi-Fagoaga (MDPI AG, 2023)
In the post-COVID-19 era, where innovation and entrepreneurship as an engine for economic development is a top priority for each country, acquiring various skills through innovation and entrepreneurship education is a trend for higher education students. We focus our analysis on two public universities in China and Spain with some similarities in the implementation of innovation and entrepreneurship education. To obtain our information, we conducted interviews with multiple experts in both universities. The study shows that both countries provide funding and policies to promote innovation and entrepreneurship education as innovation and entrepreneurship education is seen as making the university more visible, both at the national and international levels, and as providing society with employment opportunities. We conclude that although innovation and entrepreneurship education design and definition in both universities are different, their development characteristics and trends are the same. Moreover, both universities face common difficulties, namely financial support, management support, and integration with different disciplines. Finally, innovation and entrepreneurship education promote also internationalization and regional development, which requires both countries to strengthen foreign language education and the provision of more entrepreneurial support services.